Aesthetic assessment of paintings based on visual balance. Issue 14 (1st December 2019) - Li, Mao; Lv, Jiancheng; Tang, Chenwei
Abstract : All things follow the cosmic equilibrium rule. As one of the important factors in evaluating images of aesthetic effects, the visual balance has not attracted much attention. In this study, a novel method is proposed to quantify the law of visual balance and automatically evaluate the aesthetic value of images. In the proposed method, the authors first analyse the colour composition of images using the K ‐means clustering method. Then, based on information aesthetics theory and perspective principles, a calculation method is proposed to find the visual centre of gravity of images. Finally, the aesthetic effect of the image based on visual balance is evaluated according to the positional relationship between the visual centre of gravity and the physical centre of the image. With extensive experimental results, the authors demonstrate qualitatively and quantitatively that the proposed evaluation method is basically consistent with the intuitive experience of most human beings. Moreover, experiments are also conducted on a large and diversified benchmark data set that are competitive with the current state of the art.